Analysis of Impact Mitigation Policy and Greenhouse gas Reduction Strategies At Pt Xyz - Djoko Suharyanto (International Journal Labs, 2022)
Background: Environmental issues have now become a very important topic for the attention of countries around the world, especially efforts to prevent climate change by mitigating the greenhouse effect. Objective: aims to analyze the impact mitigation policies and GHG reduction strategies carried out by PT XYZ as one of the manufacturing industries that is committed to contributing to the mitigation of greenhouse gas impacts. Methods: AHP method, is affected by this assessment. Pairwise comparison matrices, or pairwise comparison matrices containing the preference levels of several options for each criterion, were used to organize the findings of this assessment. Results: which produces the highest CO2 emissions due to the use of Production Machinery in Factory 1 location of 14,599 Ton.CO2eq per year, or 37% of the total CO2 emissions in this company, then the second highest is from factory 5 location, namely 14,311 Ton.CO2 eq.